2022
DOI: 10.1038/s41598-022-19441-9
|View full text |Cite
|
Sign up to set email alerts
|

Graph-based representation for identifying individual travel activities with spatiotemporal trajectories and POI data

Abstract: Individual daily travel activities (e.g., work, eating) are identified with various machine learning models (e.g., Bayesian Network, Random Forest) for understanding people’s frequent travel purposes. However, labor-intensive engineering work is often required to extract effective features. Additionally, features and models are mostly calibrated for individual trajectories with regular daily travel routines and patterns, and therefore suffer from poor generalizability when applied to new trajectories with more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As expected, many studies have demonstrated that POIs data perform well in understanding travel activities and public preferences. Liu et al (2022) employed POIs distribution as a key Zoning of the supply and demand for beach recreation services in DPND. Li et al 10.3389/fmars.2024.1288112 node for identifying individual travel activities.…”
Section: Novel Methods Of Ces Demand Based On Pois Densitymentioning
confidence: 99%
“…As expected, many studies have demonstrated that POIs data perform well in understanding travel activities and public preferences. Liu et al (2022) employed POIs distribution as a key Zoning of the supply and demand for beach recreation services in DPND. Li et al 10.3389/fmars.2024.1288112 node for identifying individual travel activities.…”
Section: Novel Methods Of Ces Demand Based On Pois Densitymentioning
confidence: 99%
“…Similarly in [28] graph convolutional neural networks (GCNs) [18] are used to classify GPS traces of 139 subjects into 5 offline activities. GCNs are also used recently in [26] to infer 8 offline activities in GPS diaries collected and labeled by 167 subjects.…”
Section: Previous Workmentioning
confidence: 99%
“…It is well established that a user's location is indicative of the type of real-world, day-to-day activities, such as shopping and dining (Hereafter referred to as "offline activities") they perform. Research has shown that basic offline activities can be inferred from GPS traces using both conventional statistical methods [22][23][24] and machine learning algorithms [19,26,28,29]. The same has been demonstrated using mobile phone data collected city-wide at the base station level [25,30].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The second issue concerns the different POI reclassification standards, where varying standards present challenges in conducting comparisons and analogies across research studies 42,43 . Inconsistent standards can lead to unreliable results due to the potential influence of personal preferences or assumptions rather than objective evidence in the identification process 44 .…”
Section: Introductionmentioning
confidence: 99%